2021
DOI: 10.3390/ijms22115722
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Exercise and Nutraceuticals in Modulating Molecular Pathways of Osteoarthritis

Abstract: Osteoarthritis (OA) is a painful and disabling disease that affects millions of patients. Its etiology is largely unknown, but it is most likely multifactorial. OA pathogenesis involves the catabolism of the cartilage extracellular matrix and is supported by inflammatory and oxidative signaling pathways and marked epigenetic changes. To delay OA progression, a wide range of exercise programs and naturally derived compounds have been suggested. This literature review aims to analyze the main signaling pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 141 publications
(161 reference statements)
0
23
0
Order By: Relevance
“…Physical exercise would appear to play a chondroprotective role as it increases the expression levels of the cartilage synthesis markers, in addition to improving antioxidant defenses and lowering lipid peroxidation levels. However, it is important to consider that excessive or incorrect exercise could adversely affect the course of OA [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical exercise would appear to play a chondroprotective role as it increases the expression levels of the cartilage synthesis markers, in addition to improving antioxidant defenses and lowering lipid peroxidation levels. However, it is important to consider that excessive or incorrect exercise could adversely affect the course of OA [12].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines for KOA management suggest conservative treatment as the first approach to the disease. The conservative treatment aims to reduce pain and consists of the single or synergistic use of drugs such as NSAIDs, infiltrations based on corticosteroids or hyaluronic acid, focal muscle vibration (WBV), oxy-ozone therapy (O 2 -O 3 ), platelet-rich plasma injections (PRP), and mesenchymal adipose stem cell (MSC) therapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Papalia et al, subjects underwent three i.a. knee injections administered at a weekly interval with a HA hybrid formulation (intervention group) or a PRP solution (control group) [50]. In this study clinicians used a hybrid HA solution with a peculiar profile distribution into the joint due to the combination of both high and low molecular weight fractions.…”
Section: Discussionmentioning
confidence: 99%
“…On the one side, it was shown that low intensity exercise could improve antioxidant defences and lower lipid peroxidation levels [ 21 ]. On the other side, it is known that in the body of professional athletes under intense and strenuous physical exertion, oxidative stress [ 22 ] can occur, leading to the accumulation of lipid peroxidation products, including free radicals.…”
Section: Discussionmentioning
confidence: 99%